The Effects of Processing Time on the Total Phenolic, Flavonoid Content, and Antioxidant Activity of Multi Bulb and Single Bulb Black Garlic - Alfian Hendra Krisnawan; Ryanto Budiono; Albina Natarika; Arum Mirani; Novia Andarini (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Black garlic is produced by processing multi-bulb garlic (Allium sativum) or single-bulb garlic in high temperature and high humidity for several days. Black garlic has many health benefits, such as an antioxidant activity resulting from its compound, including groups of flavonoid and phenolic compounds. This study aimed to analyze the effect of aging time on multi-bulb and single-bulb black garlic on the content of total phenolic, flavonoid, and antioxidant activity. Black garlic was processed at a 60-70°C heating temperature and 70-80% relative humidity for 25 days. Determination of total phenol and flavonoid contents was conducted using spectrophotometric methods with gallic acid as a standard of total phenolic and quercetin as a standard of flavonoid, while the antioxidant activity was determined by DPPH radical reduction. The results showed that total phenolic contents (% w/w GAE), flavonoids contents (% w/w QE), and EC50 values at 0 until day 25 increased on a particular day in multi-bulb and single-bulb black garlic. The optimal total phenolic content of both black garlic was obtained by heating for 20 days, flavonoid content of multi-bulb garlic for 10 days, and single-bulb black garlic for 15 days. Highest antioxidant activity was obtained on days 20 and 25 for single-bulb black garlic and multi-bulb black garlic, respectively. The aging time of black garlic affects total phenolic, flavonoid content, and antioxidant activity. In general, longer processing time caused an increase in the total phenolic content, flavonoid content, and antioxidant activity of both black garlics. Multi-bulb black garlic showed higher phenolic or flavonoid content and antioxidant activity than single-bulb black garlic.